Is unicompartmental knee arthroplasty a better choice than total knee arthroplasty for unicompartmental osteoarthritis? A systematic review and meta-analysis of randomized controlled trials - Kuanyu Xia; Lang Min; Wenqing Xie; Guang Yang; Dong Keon Yon; Seung Won Lee; Ai Koyanagi; Louis Jacob; Lee Smith; Jae Il Shin; Masoud Rahmati; Wenfeng Xiao; et al. (Chinese Medical Journal)
Abstract. Background:. The choice of unicompartmental knee arthroplasty (UKA) vs. total knee arthroplasty (TKA) in the surgical treatment of knee osteoarthritis (KOA) remains controversial. This study aimed to perform a systematic review and meta-analysis of randomized controlled trials (RCTs) to compare the clinical results of UKA and TKA for treating unicompartmental KOA. Methods:. PubMed, Embase, and the Cochrane Library were systematically searched for articles published up to January 2, 2023. The literature was rigorously screened to include only RCTs comparing UKA and TKA for unicompartmental KOA. A systematic review and meta-analysis were performed to calculate the mean difference (MD), relative risk (RR), and 95% confidence interval (CI) according to the Cochrane standards. Results:. Thirteen publications involving 683 UKAs and 683 TKAs were analyzed. Except for one study with a follow-up period of 15 years, all outcome measures reported were within 5 years of follow-up. Meta-analysis showed better knee recovery (MD: 1.23; 95% CI: 1.01–1.45; P <0.001), greater knee function (MD: 1.78; 95% CI: 0.34–3.22; P = 0.020), less pain (MD: 0.75; 95% CI: 0.43–1.06; P <0.001), and better health status (MD: 3.75; 95% CI: 0.81–6.69; P = 0.010) after UKA than TKA. However, considering the minimal clinically important difference values for these variables, the findings were not clinically relevant. Moreover, UKA patients had fewer complications (RR: 0.59; 95% CI: 0.45–0.78; P <0.001) and shorter hospital stays (MD: –0.89; 95% CI: –1.57 to –0.22; P = 0.009) than did TKA patients. There were no statistically significant differences in terms of postoperative range of movement, revision, failure, operation time, and patient satisfaction. Conclusions:. In terms of clinical efficacy, there was no obvious advantage of UKA over TKA in the surgical treatment of knee OA when considering the minimal clinically important difference. The main advantage of UKA over TKA is that it leads to fewer complications and a shorter length of hospital stay. It is ideal to perform prospective studies with longer follow-up periods to fully evaluate the long-term efficacy and safety of the two procedures in the future.